Method for simultaneously removing carbonyl sulfide and hydrogen sulfide in coking liquefied gas
By using a series grading method of carbonylsulfide hydrolysis catalyst and acrylic fiber desulfurizer in a continuous flow fixed bed reactor, the problem of difficulty in removing carbonylsulfide and hydrogen sulfide in the coking liquefied gas at the same time is solved, and efficient resource utilization and environmental protection are achieved.
Patent Information
- Application Number
- CN202311391174.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-25
- Publication Date
- 2025-04-25
AI Technical Summary
The prior art is difficult to simultaneously effectively remove carbonyl sulfur and hydrogen sulfide generated by its hydrolysis in coking liquefied gas, resulting in waste of resources and environmental pollution.
The reaction is carried out in a continuous flow fixed bed reactor using a series grading method of carbonylsulfide hydrolysis catalyst and acrylic fiber desulfurization agent. The hydrolysis of COS is promoted through the carbonylsulfide hydrolysis catalyst, and the generated H2S is captured using acrylic fiber desulfurization agent to achieve simultaneous removal of both.
It improves the overall removal efficiency of COS and H2S in coking liquefied gas, reduces resource waste and environmental pollution, and is simple to prepare catalysts, which is suitable for industrial production.
Smart Images

Figure BDA0004512431950000031 
Figure BDA0004512431950000141 
Figure FDA0004512431940000011
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of desulfurizing agents, and in particular relates to a method for simultaneously removing carbonyl sulfide and hydrogen sulfide from coking liquefied gas. Background Art
[0002] The sulfur content of coking liquefied gas is high, and its actual application value is low. Most of it is only used as fuel, resulting in a waste of resources. The propylene content in this part of liquefied gas is about 12-17wt%, and it usually contains about 200-300ppm of carbonyl sulfide. If this part of propylene can be desulfurized and purified and used in polypropylene or butyl octanol units, the application value of coking liquefied gas can be greatly improved.
[0003] Carbonyl sulfide (COS) can corrode production equipment and damage the human nervous system. Even a small amount of COS can cause serious poisoning and inactivation of catalysts. COS can form sulfur dioxide and sulfate aerosols through photochemical reactions, thus causing acid rain and causing great damage to the ecological environment. Since COS has stable chemical properties and its acidity and polarity are weaker than hydrogen sulfide, the general method of removing hydrogen sulfide cannot completely remove COS.
[0004] At present, the commonly used COS removal methods include reduction, hydrolysis, absorption, adsorption and oxidation. 2 Reduction of COS to H 2 S, this method has a high conversion rate, but the cost is high and there are certain side reactions. The absorption method uses alkaline organic amine solution to absorb acidic COS gas. This method has a fast absorption speed and low cost, but the desulfurization selectivity is poor, the equipment is severely corroded, and the energy consumption is high. It is mainly suitable for crude desulfurization.
[0005] Functional fiber is a new type of adsorption and separation functional fiber material, which belongs to one of the rapidly developing high-tech technologies today. Compared with ion exchange resin, functional fiber material has the characteristics of high exchange capacity, large effective specific surface area and fast exchange speed. Compared with ion exchange resin, functional fiber has obvious reaction kinetics advantages, and can adsorb and separate harmful gases under gas phase conditions. Patent ZL95116025.7 prepares ion exchange fiber with acid gas adsorption by grafting triethylenetetramine with acrylic fiber; Patent CN111282380A adopts the process technology combining hydrogen peroxide spraying with ion exchange adsorption. High-concentration hydrogen sulfide gas first passes through the hydrogen peroxide spraying system with hydrogen peroxide as the spray liquid, and then the dust removal device is used to remove the sulfur element brought out by the hydrogen peroxide spraying system, and finally enters the ion exchange fiber purification unit with alkaline ion exchange fiber non-woven fabric (the fiber surface contains amino groups, quaternary ammonium groups or pyridine groups) as the purification filter layer. The hydrogen sulfide-containing waste gas penetrates the purification filter layer and achieves near-zero emissions after adsorption purification. Patent CN104984744B discloses a plant fiber-based solid amine adsorption material and its preparation method and application. The adsorption material is based on plant fibers containing lignin and cellulose, and is obtained by introducing polyethyleneimine polymers with a small molecular weight into the lignin and cellulose of the plant fibers respectively by a classification modification method. The adsorption material has good antibacterial properties and adsorption and capture properties for acidic gases, and can be regenerated by thermal desorption after adsorbing acidic gases. Patent CN1188565C discloses a chelated functional fiber and its synthesis method. The functional fiber is prepared by hydrolyzing acrylic fibers, uniformly coating polyethyleneimine on the outer surface of acrylic fibers by a chemical method, and then firmly attaching polyethyleneimine to the carrier fibers by chemical crosslinking. The fiber has stable performance of HCl, SO 2 , H 2 S and other acidic gases, and has a good purification and removal effect. Patent CN104923176B irradiates the base fiber pretreated with alkali solution with gamma rays of cobalt 60, and then obtains dendritic high-density solid amine fiber through grafting acrylic monomers, amination substitution reaction, Michael addition of amino groups and unsaturated monomers, and amide substitution chemical modification. The fiber material has high amine group density, good thermal stability and chemical stability, high adsorption capacity for acidic gases, and can be regenerated through thermal desorption cycles.
[0006] Patent CN108246298A invented a method for removing carbonyl sulfide from gas by using nano-layered solid alkali. Hydrolysis and oxidation reactions occur during the removal process. After COS is hydrolyzed, it is converted into elemental sulfur and sulfate by the oxidation of dissolved oxygen in water. The generated sulfate covers the surface of the catalyst, which easily leads to catalyst deactivation, thus requiring frequent regeneration.
[0007] Patent CN109794251A provides a method for preparing a carbonyl sulfide hydrolysis catalyst by modifying a zinc-nickel-aluminum-cerium hydrotalcite precursor with a complexing agent, wherein the method comprises preparing a zinc-nickel-aluminum-cerium salt solution and an alkaline solution; co-precipitating the salt solution and the alkaline solution to obtain a hydrotalcite precursor; adding an organic complexing agent for modification, and heat-treating the filtered precipitate to obtain the desired metal oxide catalyst. However, the hydrogen sulfide generated by COS hydrolysis cannot be removed at the same time.
[0008] Patent CN112473742A provides a desulfurization catalyst for simultaneously removing hydrogen sulfide and carbonyl sulfide and a preparation method thereof, the method comprising: dissolving a metal chelating agent salt in water, adding an organic amine, an organic alcohol, a mixed oxide and sodium carbonate in sequence, then heating to 80-90°C for reaction for 4-6 hours to obtain a catalyst solution, and drying to obtain a desulfurization catalyst for simultaneously removing hydrogen sulfide and carbonyl sulfide. However, when the catalyst of the invention is used on site, it needs to be mixed with an alkaline solution with a pH value of 9-10 to simultaneously absorb the acidic gases hydrogen sulfide and carbonyl sulfide in the gas, generating a large amount of waste liquid, which increases the difficulty of subsequent treatment. Summary of the invention
[0009] In view of the shortcomings of the prior art, the present invention aims to provide a method for simultaneously removing carbonyl sulfide and hydrogen sulfide from coking liquefied gas, which can remove carbonyl sulfide and hydrogen sulfide produced by its hydrolysis. 2 S is removed at the same time.
[0010] The method for removing carbonyl sulfide and hydrogen sulfide from coking liquefied gas of the present invention is carried out in a continuous flow fixed bed reactor. The reaction tube is a tube with an inner diameter of 30 mm, and a 3 mm thermocouple sleeve is inserted therein. The reaction tube is filled with carbonyl sulfide hydrolysis catalyst and acrylic fiber desulfurizer in sequence from bottom to top. The space velocity of the coking liquefied gas is 3000-6000h -1 , the reaction temperature is 50-70°C, and the reaction pressure is normal pressure.
[0011] The filling volume ratio of the carbonyl sulfide hydrolysis catalyst and the acrylic fiber desulfurization agent is (1-3):1.
[0012] The carbonyl sulfide hydrolysis catalyst comprises two parts: a carrier and an active component. The carrier is composed of Al-Si-Ti, and the main active components are K, Ga and La.
[0013] The carbonyl sulfide hydrolysis catalyst has a carrier of molecular sieve and titanium oxide, and active components of potassium oxide, gallium oxide and lanthanum oxide, and the composition is as follows in parts by weight:
[0014]
[0015] The molecular sieve is one or more of HY, HMCM-22 and HZSM-5.
[0016] The titanium oxide precursor is added in the form of metatitanic acid, and the potassium oxide, gallium oxide, and lanthanum oxide precursors are added in the form of potassium nitrate, gallium nitrate, and lanthanum nitrate, respectively.
[0017] The preparation method of the carbonyl sulfide hydrolysis catalyst comprises the following steps:
[0018] (1) mixing molecular sieve, metatitanic acid and an additive uniformly to form a solid material; the additive is preferably polyvinyl alcohol, Tianqing powder, or polyacrylamide;
[0019] (2) adding a binder into water and stirring to form a solution A; the binder is preferably nitric acid;
[0020] (3) Ball rolling: The solid material is placed in a ball rolling machine, and Solution A is sprayed onto the material in the ball rolling machine. The ball rolling machine is rotated to form the material until the material is formed into a sphere with a diameter of about 2 mm. The spherical particles are screened to obtain spherical particles with a diameter of 2 mm. The spherical particles are dried and roasted to obtain a spherical carrier.
[0021] (4) Impregnation: The active components potassium oxide, gallium oxide, and lanthanum oxide precursors are dissolved in water to prepare solution B, and the support is added to solution B and impregnated for 3-6 hours;
[0022] (5) Drying: Dry the impregnated carrier at a temperature of 100-130°C for 1-4 hours;
[0023] (6) Calcination: Calcinate the dried carrier at 300-600°C for 3-5h to obtain a carbonyl sulfide hydrolysis catalyst.
[0024] The preparation method of the acrylic fiber desulfurizer comprises the following steps:
[0025] (1) Amination of acrylic fiber:
[0026] Placing acrylic fiber and amino compound solution in a reaction kettle, the mass of acrylic fiber: the mass of amino compound = 1:3-1:15, the reaction temperature is 90-150° C., the reaction time is 3-8 hours, after the reaction is completed, the fiber is taken out, washed with deionized water, and dried at 50-90° C. to constant weight to obtain an aminated acrylic fiber material;
[0027] (2) Metal modification of aminated acrylic fiber:
[0028] The aminated acrylic fiber material and the metal compound solution are placed in a reaction kettle, the mass of the aminated acrylic fiber material: the mass of the metal compound solution = 1:50-1:300, the reaction temperature is 30-60°C, the reaction time is 0.5-4h, the solution pH value is 3-9, after the reaction is completed, the fiber is taken out, washed with deionized water, and dried at 50-90°C to constant weight, and the obtained metal-modified aminated acrylic fiber material is the acrylic fiber desulfurizer.
[0029] The amino compound in step (1) is one of polyethyleneamine, polyethyleneimine, triethylenetetramine, polyethylenepolyamine, 4-aminopyridine, 2-aminothiazole or 2-aminobenzothiazole.
[0030] The amino compound solution in step (1) is a methanol solution, an ethanol solution, a toluene solution, a n-hexane solution or an aqueous solution of the amino compound; preferably an aqueous solution.
[0031] The mass ratio of the acrylic fiber to the mass ratio of the amino compound is preferably 1:5-1:10, the reaction temperature is preferably 100-140° C., and the reaction time is 4-6 hours.
[0032] The metal compound solution in step (2) is a solution of one or more of copper sulfate, zinc sulfate, copper chloride, zinc chloride, potassium sulfate, sodium sulfate, potassium chloride or sodium chloride with a mass concentration of 0.01 to 5%, preferably 0.1 to 3%.
[0033] The mass of the acrylic fiber: the mass of the metal compound solution is preferably 1:50-1:200, the reaction temperature is preferably 30-40° C., the reaction time is preferably 0.5-2 h, and the solution pH is preferably 4-8.
[0034] Compared with the prior art, the present invention has the following beneficial effects:
[0035] (1) The present invention provides an integrated method for removing COS and H by using a carbonyl sulfide hydrolysis catalyst and an acrylic fiber desulfurizer in series. 2 The present invention realizes two continuous reactions in a limited space, and the loading amounts of the carbonyl sulfide hydrolysis catalyst and the acrylic fiber desulfurization agent can be flexibly adjusted according to specific circumstances.
[0036] (2) The acrylic fiber desulfurizer has a large specific surface area and abundant amino groups, which provide a large number of active sites for the reaction between hydrogen sulfide and amino groups, thereby increasing the removal rate of hydrogen sulfide. In addition, the modified metal copper and zinc on the surface of the acrylic fiber desulfurizer can capture hydrogen sulfide in the gas phase as active sites. Therefore, the combination of amino groups and metal active sites enriches the removal methods of hydrogen sulfide by the acrylic fiber desulfurizer.
[0037] (3) The hydrogen sulfide produced in the hydrolysis process can be removed in time during the reaction, breaking the COS+H 2 O=H 2 S+CO 2 The balance of the reaction is conducive to the rightward progress of the hydrolysis reaction, which increases the COS and H 2 The overall removal efficiency of S. The carbonyl sulfide hydrolysis catalyst and the acrylic fiber desulfurization agent have high activity and good stability. The catalyst preparation method of the invention is simple, and the raw materials used are all commercially available products, which is suitable for industrial large-scale production. DETAILED DESCRIPTION
[0038] The present invention is further described below in conjunction with embodiments, but the protection scope of the present invention is not limited thereto.
[0039] Unless otherwise specified, all raw materials used in the examples are commercially available.
[0040] Unless otherwise indicated, implied from the context, or customary in the prior art, all parts and percentages in this application are based on weight, and the test and characterization methods used are all current as of the filing date of this application. Where applicable, the contents of any patent, patent application or publication referred to in this application are fully incorporated herein by reference, and their equivalent patent families are also incorporated by reference, especially the definitions of synthesis techniques, product and processing designs, polymers, comonomers, initiators or catalysts disclosed in these documents in the art. If the definition of a specific term disclosed in the prior art is inconsistent with any definition provided in this application, the definition of the term provided in this application shall prevail.
[0041] Numerical ranges in this application are approximate values, so unless otherwise stated, they may include numerical values outside the range. Numerical ranges include all numerical values from the lower limit to the upper limit increased by 1 unit, provided that there is an interval of at least 2 units between any lower value and any higher value. For example, if the recorded component, physical or other properties (such as molecular weight, melt index, etc.) are 100 to 1000, it means that all single values are clearly listed, such as 100, 101, 102, etc., and all sub-ranges, such as 100 to 166, 155 to 170, 198 to 200, etc. For a range comprising a numerical value less than 1 or comprising a fraction greater than 1 (such as 1.1, 1.5, etc.), 1 unit is appropriately regarded as 0.0001, 0.001, 0.01 or 0.1. For ranges containing single digit numbers less than 10 (eg, 1 to 5), typically one unit is considered to be 0.1. These are merely specific examples of what is intended, and all possible combinations of numerical values between the lowest value and the highest value enumerated are considered to be expressly stated in this application.
[0042] When used with respect to chemical compounds, unless expressly specified otherwise, the singular includes all isomeric forms and vice versa (e.g., "hexane" includes all isomers of hexane, individually or collectively). In addition, nouns using "a," "an," or "the" also include their plural forms unless expressly specified otherwise.
[0043] The terms "comprising", "including", "having" and their derivatives do not exclude the presence of any other components, steps or processes, and are irrelevant to whether these other components, steps or processes are disclosed in this application. To eliminate any doubt, unless explicitly stated, all compositions using the terms "comprising", "including", or "having" in this application may include any additional additives, adjuvants or compounds. On the contrary, except for those necessary for operating performance, the term "essentially consisting of..." excludes any other components, steps or processes from the scope of any description of the term below. The term "consisting of..." does not include any components, steps or processes that are not specifically described or listed. Unless explicitly stated, the term "or" refers to the listed individual members or any combination thereof.
[0044] The present invention is further described below in conjunction with embodiments, and the specific embodiments and testing methods are as follows:
[0045] The sulfur content in the raw material and the purified gas was detected by a speciation sulfur analyzer. The hydrolysis rate of COS was calculated according to the following formula: Where: M 0 、M 1 represent the volume concentration of COS at the reactor inlet and outlet, respectively.
[0046] Example 1
[0047] Preparation of carbonyl sulfide hydrolysis catalyst: Weigh 667g HY molecular sieve, 157g titanic acid, and 20g polyvinyl alcohol respectively, mix them evenly to form a solid material; weigh 15g nitric acid, add it into water and stir evenly to form a solution; put the mixed solid material into a ball rolling machine, spray nitric acid solution on the material in the ball rolling machine, rotate the ball rolling machine to form small balls with a diameter of 2mm; dry the small balls at 120℃ for 6h and calcine at 400℃ for 5h to obtain a carbonyl sulfide hydrolysis catalyst carrier.
[0048] Weigh 60g of potassium nitrate, 50g of gallium nitrate and 44g of lanthanum nitrate and dissolve them in water to prepare a solution, add the carbonyl sulfide hydrolysis catalyst carrier into the solution and impregnate for 3h; dry the impregnated carrier at 130°C for 4h and calcine at 490°C for 5h to obtain carbonyl sulfide hydrolysis catalyst A.
[0049] Preparation of acrylic fiber desulfurizer: Weigh 12g acrylic fiber, add 600g aqueous solution containing 60g triethylenetetramine, and react at 100℃ for 4h. After the reaction, take out the fiber, wash it with deionized water, and dry it at 60℃ to constant weight to obtain aminated acrylic fiber material.
[0050] Weigh 12g of aminated acrylic fiber material, add 600g of an aqueous solution containing 0.6g of copper sulfate, adjust the pH value of the solution to 6, and react at 30°C for 0.5h. After the reaction, take out the fiber, wash it with deionized water, and dry it at 60°C to constant weight to obtain acrylic fiber desulfurizer A1.
[0051] Application methods of carbonyl sulfide hydrolysis catalyst and acrylic fiber desulfurization agent:
[0052] The reaction was carried out in a continuous flow fixed bed reactor. The reaction tube was a tube with an inner diameter of 30 mm and a 3 mm thermocouple sleeve inserted inside. The reaction tube was filled with carbonyl sulfide hydrolysis catalyst and acrylic fiber desulfurization agent from bottom to top. The loading amount of carbonyl sulfide hydrolysis catalyst and acrylic fiber desulfurization agent was 10 ml. The catalyst evaluation conditions were: space velocity of 3000 h -1 The reaction temperature was 50°C and the reaction pressure was normal pressure. The reaction raw material was coking liquefied gas, in which the carbonyl sulfide content was 230ppm. The COS and H in the raw material and the purified gas were detected by a morphological sulfur analyzer. 2 S content, and calculated the COS conversion rate according to the above formula. The results are shown in Table 1.
[0053] Example 2
[0054] Preparation of carbonyl sulfide hydrolysis catalyst: 561g HMCM-22 molecular sieve, 167g metatitanic acid and 41g polyvinyl alcohol were weighed respectively and mixed evenly to form a solid material; 37g nitric acid was weighed and added into water and stirred evenly to form a solution; the mixed solid material was placed in a ball rolling machine, nitric acid solution was sprayed on the material in the ball rolling machine, and the ball was rolled to form a small ball with a diameter of 2mm; the small ball was dried at 120°C for 4h and calcined at 470°C for 4h to obtain a carbonyl sulfide hydrolysis catalyst carrier.
[0055] Weigh 118 g of potassium nitrate, 69 g of gallium nitrate, and 68 g of lanthanum nitrate and dissolve them in water to prepare a solution. Add the carbonyl sulfide hydrolysis catalyst carrier into the solution and impregnate for 3 hours. Dry the impregnated carrier at 120° C. for 4 hours and calcine at 500° C. for 4 hours to obtain carbonyl sulfide hydrolysis catalyst B.
[0056] Preparation of acrylic fiber desulfurizer: Weigh 15g acrylic fiber, add 810g aqueous solution containing 90g polyethyleneimine, and react at 130℃ for 4h. After the reaction, take out the fiber, wash it with deionized water, and dry it at 60℃ to constant weight to obtain aminated acrylic fiber material.
[0057] Weigh 15g of aminated acrylic fiber material, add 750g of an aqueous solution containing 3g of copper sulfate, adjust the pH value of the solution to 7, and react at 30°C for 1h. After the reaction, take out the fiber, wash it with deionized water, and dry it at 60°C to constant weight to obtain acrylic fiber desulfurizer B1.
[0058] Application methods of carbonyl sulfide hydrolysis catalyst and acrylic fiber desulfurization agent:
[0059] The reaction was carried out in a continuous flow fixed bed reactor. The reaction tube was a tube with an inner diameter of 30 mm and a 3 mm thermocouple sleeve inserted inside. The reaction tube was filled with carbonyl sulfide hydrolysis catalyst and acrylic fiber desulfurization agent from bottom to top. The loading amount of carbonyl sulfide hydrolysis catalyst and acrylic fiber desulfurization agent was 10 ml. The catalyst evaluation conditions were: space velocity of 3000 h -1 The reaction temperature was 50°C and the reaction pressure was normal pressure. The reaction raw material was coking liquefied gas, in which the carbonyl sulfide content was 230ppm. The COS and H in the raw material and the purified gas were detected by a morphological sulfur analyzer. 2 S content, and calculated the COS conversion rate according to the above formula. The results are shown in Table 1.
[0060] Example 3
[0061] Preparation of carbonyl sulfide hydrolysis catalyst: 881g HZSM-5 molecular sieve, 257g metatitanic acid, and 42g Tianqing powder were weighed respectively, and mixed evenly to form a solid material; 31g nitric acid was weighed and added to water and stirred evenly to form a solution; the mixed solid material was placed in a ball rolling machine, nitric acid solution was sprayed on the material in the ball rolling machine, and the ball was rolled to form a small ball with a diameter of 2mm; the small ball was dried at 100°C for 4h and calcined at 510°C for 4h to obtain a carbonyl sulfide hydrolysis catalyst carrier.
[0062] Weigh 72g potassium nitrate, 79g gallium nitrate and 85g lanthanum nitrate and dissolve them in water to prepare a solution, add the carbonyl sulfide hydrolysis catalyst carrier into the solution and immerse for 3h; dry the impregnated carrier at 120℃ for 4h and calcine at 500℃ for 4h to obtain carbonyl sulfide hydrolysis catalyst C.
[0063] Preparation of acrylic fiber desulfurizer: Weigh 20g acrylic fiber, add 1000g aqueous solution containing 120g 4-aminopyridine, and react at 140℃ for 6h. After the reaction, take out the fiber, wash it with deionized water, and dry it at 70℃ to constant weight to obtain aminated acrylic fiber material.
[0064] Weigh 20g of aminated acrylic fiber material, add 1000g of aqueous solution containing 1g of zinc sulfate, adjust the pH value of the solution to 7, and react at 30°C for 1h. After the reaction, take out the fiber, wash it with deionized water, and dry it at 70°C to constant weight to obtain acrylic fiber desulfurizer C1.
[0065] Application methods of carbonyl sulfide hydrolysis catalyst and acrylic fiber desulfurization agent:
[0066] Catalyst application method:
[0067] The reaction was carried out in a continuous flow fixed bed reactor. The reaction tube was a tube with an inner diameter of 30 mm and a 3 mm thermocouple sleeve inserted inside. The reaction tube was filled with carbonyl sulfide hydrolysis catalyst and acrylic fiber desulfurization agent from bottom to top. The loading amount of carbonyl sulfide hydrolysis catalyst and acrylic fiber desulfurization agent was 10 ml. The catalyst evaluation conditions were: space velocity of 3000 h -1 The reaction temperature was 50°C and the reaction pressure was normal pressure. The reaction raw material was coking liquefied gas, in which the carbonyl sulfide content was 230ppm. The COS and H in the raw material and the purified gas were detected by a morphological sulfur analyzer. 2 S content, and calculated the COS conversion rate according to the above formula. The results are shown in Table 1.
[0068] Example 4
[0069] Preparation of carbonyl sulfide hydrolysis catalyst: 679g HZSM-5 molecular sieve, 181g metatitanic acid and 34g polyacrylamide were weighed respectively and mixed evenly to form a solid material; 31g nitric acid was weighed and added into water and stirred evenly to form a solution; the evenly mixed solid material was placed in a ball rolling machine, nitric acid solution was sprayed on the material in the ball rolling machine, and the ball was rolled to form a small ball with a diameter of 2mm; the small ball was dried at 100°C for 4h and calcined at 600°C for 4h to obtain a carbonyl sulfide hydrolysis catalyst carrier.
[0070] Weigh 63 g of potassium nitrate, 93 g of gallium nitrate, and 78 g of lanthanum nitrate and dissolve them in water to prepare a solution. Add the carbonyl sulfide hydrolysis catalyst carrier into the solution and impregnate for 3 hours. Dry the impregnated carrier at 120° C. for 4 hours and calcine at 550° C. for 4 hours to obtain carbonyl sulfide hydrolysis catalyst D.
[0071] Preparation of acrylic fiber desulfurizer: Weigh 20g acrylic fiber, add 1300g aqueous solution containing 150g 2-aminobenzothiazole, and react at 130℃ for 6h. After the reaction, take out the fiber, wash it with deionized water, and dry it at 70℃ to constant weight to obtain aminated acrylic fiber material.
[0072] Weigh 20g of aminated acrylic fiber material, add 2000g of aqueous solution containing 10g of zinc sulfate and 7g of copper sulfate, adjust the pH value of the solution to 7, and react at 30°C for 1h. After the reaction, take out the fiber, wash it with deionized water, and dry it at 70°C to constant weight to obtain acrylic fiber desulfurizer D1.
[0073] Application methods of carbonyl sulfide hydrolysis catalyst and acrylic fiber desulfurization agent:
[0074] The reaction was carried out in a continuous flow fixed bed reactor. The reaction tube was a tube with an inner diameter of 30 mm and a 3 mm thermocouple sleeve inserted inside. The reaction tube was filled with carbonyl sulfide hydrolysis catalyst and acrylic fiber desulfurization agent from bottom to top. The loading amount of carbonyl sulfide hydrolysis catalyst and acrylic fiber desulfurization agent was 10 ml. The catalyst evaluation conditions were: space velocity of 3000 h -1 The reaction temperature was 50°C and the reaction pressure was normal pressure. The reaction raw material was coking liquefied gas, in which the carbonyl sulfide content was 230ppm. The COS and H in the raw material and the purified gas were detected by a morphological sulfur analyzer. 2 S content, and calculated the COS conversion rate according to the above formula. The results are shown in Table 1.
[0075] Example 5
[0076] Preparation of carbonyl sulfide hydrolysis catalyst: 769g HZSM-5 molecular sieve, 104g metatitanic acid and 14g polyacrylamide were weighed respectively, and mixed evenly to form a solid material; 28g nitric acid was weighed and added into water, and stirred evenly to form a solution; the evenly mixed solid material was placed in a ball rolling machine, and the material in the ball rolling machine was sprayed with nitric acid solution, and the ball was rolled to form a small ball with a diameter of 2mm; the small ball was dried at 110°C for 3h and calcined at 600°C for 4h to obtain a carbonyl sulfide hydrolysis catalyst carrier.
[0077] Weigh 85 g of potassium nitrate, 54 g of gallium nitrate, and 58 g of lanthanum nitrate and dissolve them in water to prepare a solution. Add the carbonyl sulfide hydrolysis catalyst carrier into the solution and impregnate for 3 hours. Dry the impregnated carrier at 120° C. for 4 hours and calcine at 550° C. for 4 hours to obtain carbonyl sulfide hydrolysis catalyst E.
[0078] Preparation of acrylic fiber desulfurizer: Weigh 30g acrylic fiber, add 1500g aqueous solution containing 300g polyethylene amine, and react at 110℃ for 6h. After the reaction, take out the fiber, wash it with deionized water, and dry it at 70℃ to constant weight to obtain aminated acrylic fiber material.
[0079] Weigh 20g of aminated acrylic fiber material, add 6000g of aqueous solution containing 6g of zinc sulfate, adjust the pH value of the solution to 7, and react at 40°C for 1h. After the reaction, take out the fiber, wash it with deionized water, and dry it at 70°C to constant weight to obtain acrylic fiber desulfurizer E1.
[0080] Application methods of carbonyl sulfide hydrolysis catalyst and acrylic fiber desulfurization agent:
[0081] The reaction was carried out in a continuous flow fixed bed reactor. The reaction tube was a tube with an inner diameter of 30 mm and a 3 mm thermocouple sleeve inserted inside. The loading amount of carbonyl sulfide hydrolysis catalyst and acrylic fiber desulfurization agent was 10 ml. The catalyst evaluation conditions were: space velocity of 3000 h -1The reaction temperature was 50°C and the reaction pressure was normal pressure. The reaction raw material was coking liquefied gas, in which the carbonyl sulfide content was 230ppm. The COS and H in the raw material and the purified gas were detected by a morphological sulfur analyzer. 2 S content, and calculated the COS conversion rate according to the above formula. The results are shown in Table 1.
[0082] Example 6
[0083] Preparation of carbonyl sulfide hydrolysis catalyst: 772g HZSM-5 molecular sieve, 171g metatitanic acid and 19g Tianqing powder were weighed respectively, and mixed evenly to form a solid material; 21g nitric acid was weighed and added into water and stirred evenly to form a solution; the mixed solid material was placed in a ball rolling machine, nitric acid solution was sprayed on the material in the ball rolling machine, and the ball was rolled to form a small ball with a diameter of 2mm; the small ball was dried at 120℃ for 3h and calcined at 550℃ for 3h to obtain a carbonyl sulfide hydrolysis catalyst carrier.
[0084] Weigh 60g of potassium nitrate, 107g of gallium nitrate and 91g of lanthanum nitrate and dissolve them in water to prepare a solution, add the carbonyl sulfide hydrolysis catalyst carrier into the solution and impregnate for 3h; dry the impregnated carrier at 120°C for 4h and calcine at 550°C for 4h to obtain carbonyl sulfide hydrolysis catalyst F.
[0085] Preparation of acrylic fiber desulfurizer: Weigh 20g acrylic fiber, add 1800g aqueous solution containing 200g polyethylene amine, and react at 110℃ for 6h. After the reaction, take out the fiber, wash it with deionized water, and dry it at 70℃ to constant weight to obtain aminated acrylic fiber material.
[0086] Weigh 20g of aminated acrylic fiber material, add 2000g of aqueous solution containing 10g of zinc sulfate and 15g of copper sulfate, adjust the pH value of the solution to 7, and react at 40°C for 1h. After the reaction, take out the fiber, wash it with deionized water, and dry it at 70°C to constant weight to obtain acrylic fiber desulfurizer F1.
[0087] Application methods of carbonyl sulfide hydrolysis catalyst and acrylic fiber desulfurization agent:
[0088] The reaction was carried out in a continuous flow fixed bed reactor. The reaction tube was a tube with an inner diameter of 30 mm and a 3 mm thermocouple sleeve inserted inside. The reaction tube was filled with carbonyl sulfide hydrolysis catalyst and acrylic fiber desulfurization agent from bottom to top. The loading amount of carbonyl sulfide hydrolysis catalyst and acrylic fiber desulfurization agent was 10 ml. The catalyst evaluation conditions were: space velocity of 3000 h -1 The reaction temperature was 50°C and the reaction pressure was normal pressure. The reaction raw material was coking liquefied gas, in which the carbonyl sulfide content was 230ppm. The COS and H in the raw material and the purified gas were detected by a morphological sulfur analyzer. 2S content, and calculated the COS conversion rate according to the above formula. The results are shown in Table 1.
[0089] Example 7
[0090] Preparation of carbonyl sulfide hydrolysis catalyst: 430g HZSM-5, 320g HMCM-22 molecular sieve, 171g titanic acid, and 19g polyvinyl alcohol were weighed respectively, and mixed evenly to form a solid material; 18g nitric acid was weighed and added into water and stirred evenly to form a solution; the mixed solid material was placed in a ball rolling machine, nitric acid solution was sprayed on the material in the ball rolling machine, and the ball was rolled to form a small ball with a diameter of 2mm; the small ball was dried at 120°C for 3h and calcined at 580°C for 3h to obtain a carbonyl sulfide hydrolysis catalyst carrier.
[0091] Weigh 60g of potassium nitrate, 107g of gallium nitrate and 91g of lanthanum nitrate and dissolve them in water to prepare a solution, add the carbonyl sulfide hydrolysis catalyst carrier into the solution and impregnate for 3h; dry the impregnated carrier at 120°C for 4h and calcine at 550°C for 4h to obtain carbonyl sulfide hydrolysis catalyst G.
[0092] Preparation of acrylic fiber desulfurizer: Weigh 18g of acrylic fiber, add 900g of aqueous solution containing 110g of polyethyleneimine, and react at 120℃ for 6h. After the reaction, take out the fiber, wash it with deionized water, and dry it at 70℃ to constant weight to obtain aminated acrylic fiber material.
[0093] Weigh 18g of aminated acrylic fiber material, add 1800g of an aqueous solution containing 16g of zinc sulfate and 10g of copper sulfate, adjust the pH value of the solution to 8, and react at 40°C for 1h. After the reaction, take out the fiber, wash it with deionized water, and dry it at 70°C to constant weight to obtain acrylic fiber desulfurizer G1.
[0094] Application methods of carbonyl sulfide hydrolysis catalyst and acrylic fiber desulfurization agent:
[0095] The reaction was carried out in a continuous flow fixed bed reactor. The reaction tube was a tube with an inner diameter of 30 mm and a 3 mm thermocouple sleeve inserted inside. The reaction tube was filled with carbonyl sulfide hydrolysis catalyst and acrylic fiber desulfurization agent from bottom to top. The loading amount of carbonyl sulfide hydrolysis catalyst and acrylic fiber desulfurization agent was 10 ml. The catalyst evaluation conditions were: space velocity of 3000 h -1 The reaction temperature was 50°C and the reaction pressure was normal pressure. The reaction raw material was coking liquefied gas, in which the carbonyl sulfide content was 230ppm. The COS and H in the raw material and the purified gas were detected by a morphological sulfur analyzer. 2 S content, and calculated the COS conversion rate according to the above formula. The results are shown in Table 1.
[0096] Comparative Example 1
[0097] This comparative example does not adopt the grading scheme of carbonyl sulfide hydrolysis catalyst and acrylic fiber desulfurization agent, but only adopts carbonyl sulfide hydrolysis agent without adding acrylic fiber desulfurization agent.
[0098] Preparation of carbonyl sulfide hydrolysis catalyst: 430g HZSM-5, 320g HMCM-22 molecular sieve, 171g titanic acid, and 19g polyvinyl alcohol were weighed respectively, and mixed evenly to form a solid material; 18g nitric acid was weighed and added into water and stirred evenly to form a solution; the mixed solid material was placed in a ball rolling machine, nitric acid solution was sprayed on the material in the ball rolling machine, and the ball was rolled to form a small ball with a diameter of 2mm; the small ball was dried at 120°C for 3h and calcined at 580°C for 3h to obtain a carbonyl sulfide hydrolysis catalyst carrier.
[0099] Weigh 60g of potassium nitrate, 107g of gallium nitrate and 91g of lanthanum nitrate and dissolve them in water to prepare a solution, add the carbonyl sulfide hydrolysis catalyst carrier into the solution and impregnate for 3h; dry the impregnated carrier at 120°C for 4h, and calcine at 550°C for 4h to obtain the carbonyl sulfide hydrolysis catalyst H.
[0100] Catalyst application method:
[0101] The reaction was carried out in a continuous flow fixed bed reactor. The reaction tube was a tube with an inner diameter of 30 mm and a 3 mm thermocouple sleeve inserted inside. The catalyst loading was 10 ml. The catalyst evaluation conditions were: space velocity of 3000 h -1 The reaction temperature was 50°C and the reaction pressure was normal pressure. The reaction raw material was coking liquefied gas, in which the carbonyl sulfide content was 230ppm. The COS and H in the raw material and the purified gas were detected by a morphological sulfur analyzer. 2 S content, and calculated the COS conversion rate according to the above formula. The results are shown in Table 1.
[0102] Comparative Example 2
[0103] This comparative example does not adopt the grading scheme of carbonyl sulfide hydrolysis catalyst and acrylic fiber desulfurization agent, but only adopts acrylic fiber desulfurization agent without adding carbonyl sulfide hydrolysis agent.
[0104] Preparation method of catalyst:
[0105] Preparation of acrylic fiber desulfurizer: Weigh 20g acrylic fiber, add 110g aqueous solution containing 900g polyethyleneimine, and react at 120℃ for 6h. After the reaction, take out the fiber, wash it with deionized water, and dry it at 70℃ to constant weight to obtain aminated acrylic fiber material.
[0106] Weigh 18g of aminated acrylic fiber material, add 1800g of an aqueous solution containing 16g of zinc sulfate and 10g of copper sulfate, adjust the pH value of the solution to 8, and react at 40°C for 1h. After the reaction, take out the fiber, wash it with deionized water, and dry it at 70°C to constant weight to obtain acrylic fiber desulfurizer I.
[0107] Catalyst application method:
[0108] The reaction was carried out in a continuous flow fixed bed reactor. The reaction tube was a tube with an inner diameter of 30 mm and a 3 mm thermocouple sleeve inserted inside. The loading amount of the acrylic fiber desulfurizer was 10 ml. The catalyst evaluation conditions were: the space velocity was 3000 h -1 The reaction temperature was 50°C and the reaction pressure was normal pressure. The reaction raw material was coking liquefied gas, in which the carbonyl sulfide content was 230ppm. The COS and H in the raw material and the purified gas were detected by a morphological sulfur analyzer. 2 S content, and calculated the COS conversion rate according to the above formula. The results are shown in Table 1.
[0109] Table 1 Catalyst hydrolysis activity
[0110]
[0111] Each embodiment in this specification is described in a progressive manner, and the same or similar parts between the embodiments can be referred to each other, and each embodiment focuses on the differences from other embodiments. In particular, for the system embodiment, since it is basically similar to the method embodiment, the description is relatively simple, and the relevant parts can be referred to the partial description of the method embodiment.
[0112] The above description is only an embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent substitution, improvement, etc. made within the spirit and principle of the present invention should be included in the scope of the claims of the present invention.
Claims
1. A method for simultaneously removing carbonyl sulfide and hydrogen sulfide from coking liquefied gas, characterized in that: The reaction is carried out in a continuous flow fixed bed reactor. The reaction tube is filled with carbonyl sulfide hydrolysis catalyst and acrylic fiber desulfurization agent from bottom to top. The coking liquefied gas space velocity is 3000-6000h -1 , the reaction temperature is 50-70°C, and the reaction pressure is normal pressure.
2. The method for simultaneously removing carbonyl sulfide and hydrogen sulfide from coking liquefied gas according to claim 1, characterized in that: The filling volume ratio of the carbonyl sulfide hydrolysis catalyst and the acrylic fiber desulfurization agent is (1-3):
1.
3. The method for simultaneously removing carbonyl sulfide and hydrogen sulfide from coking liquefied gas according to claim 1, characterized in that: The carbonyl sulfide hydrolysis catalyst has a carrier of molecular sieve and titanium oxide, and active components of potassium oxide, gallium oxide and lanthanum oxide, and the composition is as follows in parts by weight:
4. The method for simultaneously removing carbonyl sulfide and hydrogen sulfide from coking liquefied gas according to claim 3, characterized in that: The molecular sieve is one or more of HY, HMCM-22 and HZSM-5.
5. The method for simultaneously removing carbonyl sulfide and hydrogen sulfide from coking liquefied gas according to claim 3, characterized in that: The titanium oxide precursor is added in the form of metatitanic acid, and the potassium oxide, gallium oxide, and lanthanum oxide precursors are added in the form of potassium nitrate, gallium nitrate, and lanthanum nitrate, respectively.
6. The method for simultaneously removing carbonyl sulfide and hydrogen sulfide from coking liquefied gas according to claim 3, characterized in that: The preparation method of the carbonyl sulfide hydrolysis catalyst comprises the following steps: (1) mixing molecular sieve, titanium oxide precursor and additive uniformly to form a solid material; (2) Add the binder into water and stir evenly to prepare solution A; (3) Ball rolling: placing the solid material in a ball rolling machine, spraying solution A on the material in the ball rolling machine, rotating the ball rolling machine to form the ball, screening the spherical particles, drying and roasting the spherical particles to obtain a spherical carrier; (4) Impregnation: The active components potassium oxide, gallium oxide, and lanthanum oxide precursors are dissolved in water to prepare solution B, and the support is added to solution B and impregnated for 3-6 hours; (5) Drying: Dry the impregnated carrier at a temperature of 100-130°C for 1-4 hours; (6) Calcination: Calcinate the dried carrier at 300-600°C for 3-5h to obtain a carbonyl sulfide hydrolysis catalyst.
7. The method for simultaneously removing carbonyl sulfide and hydrogen sulfide from coking liquefied gas according to claim 1, characterized in that: The preparation method of the acrylic fiber desulfurizer comprises the following steps: (1) Amination of acrylic fiber: Placing acrylic fiber and amino compound solution in a reaction kettle, the mass of acrylic fiber: the mass of amino compound = 1:3-1:15, the reaction temperature is 90-150°C, the reaction time is 3-8h, after the reaction is completed, the fiber is taken out, washed, and dried to obtain an aminated acrylic fiber material; (2) Metal modification of aminated acrylic fiber: The aminated acrylic fiber material and the metal compound solution are placed in a reaction kettle, the mass of the aminated acrylic fiber material: the mass of the metal compound solution = 1:50-1:300, the reaction temperature is 30-60°C, the reaction time is 0.5-4h, the solution pH value is 3-9, after the reaction is completed, the fiber is taken out, washed, and dried, and the obtained metal-modified aminated acrylic fiber material is the acrylic fiber desulfurizer.
8. The method for simultaneously removing carbonyl sulfide and hydrogen sulfide from coking liquefied gas according to claim 7, characterized in that: The amino compound in step (1) is one of polyethyleneamine, polyethyleneimine, triethylenetetramine, polyethylenepolyamine, 4-aminopyridine, 2-aminothiazole or 2-aminobenzothiazole.
9. The method for simultaneously removing carbonyl sulfide and hydrogen sulfide from coking liquefied gas according to claim 7, characterized in that: The amino compound solution in step (1) is a methanol solution, an ethanol solution, a toluene solution, a n-hexane solution or an aqueous solution of the amino compound.
10. The method for simultaneously removing carbonyl sulfide and hydrogen sulfide from coking liquefied gas according to claim 7, characterized in that: The metal compound solution in step (2) is a solution of one or more of copper sulfate, zinc sulfate, copper chloride, zinc chloride, potassium sulfate, sodium sulfate, potassium chloride or sodium chloride with a mass concentration of 0.01 to 5%.
Citation Information
Patent Citations
A kind of dendritic high-density solid amine fiber material and preparation method thereof
CN104923176B
A kind of plant fiber-based solid amine adsorption material and its preparation method and application
CN104984744B
Method for removing carbonyl sulfide by nanometer laminated solid alkali
CN108246298A
Method for preparing carbonyl sulfide hydrolysis catalyst through complexing agent modified zinc-nickel-aluminum-cerium hydrotalcite-like precursor
CN109794251A
Treatment process and treatment device for high-concentration hydrogen sulfide gas
CN111282380A